Towards closing the data gap: A project-driven distributed energy resource dataset for the U.S. Grid - Haider, Rabab; Xu, Yixing; Yang, Weiwei (AMC International conference on Future of Energy Systems, 2023)
Designing future energy systems with high penetrations of variable renewable energy and third-party owned devices requires information with high spatial and temporal granularity. Existing public datasets focus on specific resource classes (ex. bulk generators, residential solar, or electric vehicles), and cannot inform holistic planning or policy decisions. Further, with the high penetration of distributed energy resources (DERs) located in the distribution grid, datasets and models which focus only on the bulk system will no longer be sufficient. To meet this modelling need, this paper presents a project-driven dataset of DERs for the contiguous U.S., generated using only publicly available data. We integrate the resources into a high-resolution test system of the U.S. grid. Our integrated U.S. grid model and DER dataset enables planners, operators, and policy makers to pose questions and conduct data-driven analysis of rapid decarbonization pathways for the electricity system. We pose a set of research questions in our Research Project Database.